Questionnaire survey on treatment planning techniques for lung stereotactic body radiotherapy in Japan. (17th December 2019) - Ueda, Yoshihiro; Takakura, Toru; Ota, Seiichi; Kito, Satoshi; Sasaki, Koji; Shimizu, Hidetoshi; Tatsumi, Daisaku; Yano, Shinsuke; Nakamura, Mitsuhiro
ABSTRACT: This study aimed to obtain details regarding treatment planning techniques for lung stereotactic body radiation therapy (SBRT) employed at each institution in Japan by using a questionnaire survey. An Internet questionnaire survey on SBRT procedures performed in 2016 was conducted by the QA/QC committee of the Japan Society of Medical Physics from April to June 2017. The questionnaire assessed two aspects: the environment for SBRT at each institution and the treatment planning techniques with and without respiratory motion management techniques (RMMT). Of the 309 evaluated responses, 218 institutions had performed SBRT. A total of 186 institutions performed SBRT without RMMT and 139 institutions performed SBRT with RMMT. When respiratory motion was ≥10 mm, 69 institutions applied RMMT. The leading RMMT were breath holding (77 institutions), respiratory gating (49 institutions) and real-time tumor tracking (11 institutions). The most frequently used irradiation technique was 3D conformal radiotherapy, which was used in 145 institutions without RMMT and 119 institutions with RMMT. Computed tomography (CT) images acquired under free breathing were mostly used for dose calculation for patients treated without RMMT. The usage ratio of IMRT/VMAT to SBRT is low in Japan, compared to elsewhere in the world (<20% vs ≥70%). Among the available dose calculation algorithms, superposition convolution was the most frequently used regardless of RMMT; however, 2% of institutions have not yet made heterogeneity corrections. In the prescription setting, about half of the institutions applied point prescriptions. The survey results revealed the most frequently used conditions, which may facilitate standardization of treatment techniques in lung SBRT.